Enhancing teaching and learning through the incorporation of generic skills for civil engineering undergraduates - Mohammad, Shahrin; Md. Nor, Hasanan; Omar, Wahid; Mohamed, Danial (2004)
In facing the challenging and competitive environment, the institutions of higher learning must constantly keep abreast with the needs of the engineering workforce at the industries. Engineering graduates who are competent with certain skills may be able to secure employment without great difficulty. Such skills are well-known as generic skills. It has been increasingly important in most developed countries over one decade ago because it assists graduates to function effectively in today's era of globalisation and the challenging world ahead. Firstly, this paper outlines the definitions and importance of the attributes of generic skills. Secondly, it discusses on the experiences in implementing generic skills in several countries across the continents as well as the local scenarios. Upon realising the importance of generic skills, Fakulti Kejuruteraan Awam (FKA) of Universiti Teknologi Malaysia (UTM) has embarked on an exercise to incorporate such skills in the teaching and learning of civil engineering course subjects at the undergraduate level. This paper also discusses on some stages of development in incorporating such skills that have already been taken place at the faculty. The experiences and challenges in the planning, implementation and assessment stages are also elaborated. Finally, this paper makes some recommendations in respect of further works that can be very valuable in order to boost up the employability of civil engineering graduates.